2017
DOI: 10.21608/adjalexu.2017.57856
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Autogenous Fresh Demineralized Tooth Graft Prepared at Chairside for Dental Implant (Clinical and Histological Study)

Abstract: INTRODUCTION:Although, the chemical composition of dentin is similar to bone, extracted teeth are still considered a clinical waste and therefore being discarded. With successful extraction of growth factors and bone morphogenic proteins (BMPs) from mammalian teeth, many researchers have supported development of a bone substitute using tooth-derived substances. OBJECTIVES: To evaluate clinical, radiological and histological efficiency of autogenous fresh demineralized tooth (AFDT) graft prepared at the chairsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The percentage increase in implant stability in the demineralized dentin graft group was statistically significantly higher than in the β-tri calcium phosphate group (p<.001). The percentage increase in the demineralized dentin graft group was more than 20%, which agrees with that reported by El-Said et al (15) , in their single-arm clinical trial, who reported a 15% increase in the mean OSSTELL score at six months postoperatively in comparison to the time of implant placement. Rawat et al ( 12), (16) reported that β-TCP appears unsuitable and not advantageous as a bone filler in immediate implant placement due to its slow bone formation and integration and inability to condense appropriately.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The percentage increase in implant stability in the demineralized dentin graft group was statistically significantly higher than in the β-tri calcium phosphate group (p<.001). The percentage increase in the demineralized dentin graft group was more than 20%, which agrees with that reported by El-Said et al (15) , in their single-arm clinical trial, who reported a 15% increase in the mean OSSTELL score at six months postoperatively in comparison to the time of implant placement. Rawat et al ( 12), (16) reported that β-TCP appears unsuitable and not advantageous as a bone filler in immediate implant placement due to its slow bone formation and integration and inability to condense appropriately.…”
Section: Discussionsupporting
confidence: 91%
“…The percentage increase in bone density in the present study is more than 15% in the demineralized dentin graft group and about 7% in the β-TCP. El-Said et al (15) reported a 39% increase in mean bone density six months after implant placement compared to preoperative values. Radiographic examination showed that all implants were fully osseointegrated with no signs of bone resorption.…”
Section: Discussionmentioning
confidence: 97%
“…To save time, smart dentine grinders integrate the grinding and sieving procedures; nonetheless, they create calcified autogenous dentine grafts. However, they have the disadvantage of lacking the demineralization phase, which is required to expose the biological dentine matrix and growth factors that drive bone production, leading in a prolonged healing period for bone (22). Also, the usage of acetic acid and pareacetic acid has affected the bacterial effect development in the autogenus fresh demineralize tooth (AFDT) graft owing to its strong oxidizing activity, which oxidizes the exterior cell walls of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the usage of acetic acid and pareacetic acid has affected the bacterial effect development in the autogenus fresh demineralize tooth (AFDT) graft owing to its strong oxidizing activity, which oxidizes the exterior cell walls of microorganisms. Proteins will be denatured, cell wall permeability will be compromised, and sulfhydral and sulphur linkages in proteins, enzymes, and other metabolites will be oxidized, causing microorganisms to quickly deactivate (22). In the presence of organic materials, peracetic acid at 200-500 ppm will inactivate grampositive and gram-negative bacteria, fungi, and yeasts in 5 minutes (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation